People Without History India's Muslim Ghettos - Seabrook, Jeremy (Pluto Press, 2011)
The West has become obsessed with Muslims, constantly classifying them as either 'moderate' or 'extreme'. Reacting against this dehumanising tendency, Jeremy Seabrook and Imran Ahmed Siddiqui show us the daily life of poor Muslims in India and sheds light on what lies behind India's 'economic miracle'. The authors examine life in Muslim communities in Kolkata, home to some of the most disadvantaged people in India, giving a voice to their views, values and feelings. We see that Muslims are no different from those of other faiths - work, family and survival are the overwhelming preoccupations of the vast majority. Although most are observant in their religion, there is no trace of the malevolence or poverty-fuelled extremism attributed to them. This enlightening and elegantly written book will be of great interest to students and practitioners of development and anyone who wants a more realistic picture of Muslim life and modern India.